2020
DOI: 10.3233/sw-200385
|View full text |Cite
|
Sign up to set email alerts
|

BOT: The building topology ontology of the W3C linked building data group

Abstract: Actors in the Architecture, Engineering, Construction, Owner and Operation (AECOO) industry traditionally exchange building models as files. The Building Information Modelling (BIM) methodology advocates the seamless exchange of all information between related stakeholders using digital technologies. The ultimate evolution of the methodology, BIM Maturity Level 3, envisions interoperable, distributed, web-based, interdisciplinary information exchange among stakeholders across the life-cycle of buildings. The W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(57 citation statements)
references
References 35 publications
0
57
0
Order By: Relevance
“…Recent research (Senthilvel et al 2020 has shown that in the future information management in the AECO industries will be cloud-based and decoupled from files. To achieve more interoperability between ontologies, alignments with existing ontologies such as BMAT, BROT (Hamdan & Scherer 2020) or BOT (Rasmussen et al 2020) should further be considered. The BMAT ontology also describes materials in the context of bridges but has not been considered for the ontology development in this approach, as it does not fulfill the complex requirements of the documentation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research (Senthilvel et al 2020 has shown that in the future information management in the AECO industries will be cloud-based and decoupled from files. To achieve more interoperability between ontologies, alignments with existing ontologies such as BMAT, BROT (Hamdan & Scherer 2020) or BOT (Rasmussen et al 2020) should further be considered. The BMAT ontology also describes materials in the context of bridges but has not been considered for the ontology development in this approach, as it does not fulfill the complex requirements of the documentation process.…”
Section: Discussionmentioning
confidence: 99%
“…This common vocabulary for ontology modeling (Motik et al 2012) makes these ontologies and their instance data easily machine-interpretable. One of the constructionspecific ontologies is the Building Topology Ontology (BOT) presented by Rasmussen et al (2020), which provides a high-level approach to model the topology of buildings. As an addition, Hamdan & Scherer (2020) demonstrated an alignable sibling of the BOT for bridges, which is available as the Bridge Topology Ontology (BROT) including components and materials.…”
Section: Related Workmentioning
confidence: 99%
“…The Building Topology Ontology (BOT) upper ontology is designed so that modelers can represent the core topological concepts of a building by defining relationships between sub-components contained within [128]. BOT was started in 2019 and is developed and maintained by the W3C Linked Building Data Community Group to provide a minimal ontology for describing relationships between a building's sub-components but is not a formal W3C standard [129].…”
Section: Building Topology Ontology (Bot)mentioning
confidence: 99%
“…An ontology is a vocabulary based method for defining the concepts and relationships used to describe an area of concern based on RDF (Resource Description Framework) [14]. A few of specific ontologies have been proposed for the domain of smart homes and buildings [11,[15][16][17][18][19]. Most of these ontologies focus on realizing specific applications like energy management [18][19][20], or automated design and operation [11,[16][17][18][19].…”
Section: Modeling Tool Of Spatial Graphmentioning
confidence: 99%
“…However, it does not provide sufficient information on spatial relationships among the sensors and other building assets. The Building Topology Ontology (BOT) [17] defines the relationships between the sub-components of a building. It also follows general W3C principles and was suggested as an extensible baseline for reuse.…”
Section: Modeling Tool Of Spatial Graphmentioning
confidence: 99%